Nonlinearity Tests For Bilinear Time Series Data - Mohamed, Ibrahim; Zaharim, Azami; Yahya, Mohd. Sahar (Penerbit UTM Press, 2005)

(untitled)
This Paper Discusses Two Nonlinearity Tests In Time Series Analysis, Which Are The Keenan’s Test And F-Test. The Tests Are Based On Time Domain Approach And Are Computationally Less Complex Than The Frequency Domain Approach. Both Tests Are Especially Suitable For Data Generated From Bilinear Model As Both Can Be Expressed In Volterra Expansion Form. In This Study, Programs For Both Tests Are Developed In S-Plus 2000 Package. Through Simulation Studies, It Will Be Shown That The Tests Work Well To Distinguish Linear From Nonlinear Data Set Generated From Bilinear Model. The Nonlinearity Tests Were Applied On Four Real Data Sets Which Have Nonlinear Characteristics And The Results Obtained Are Desirable.